Improving Performance of Electrospun Nylon 6,6 Nanofiber Membrane for Produced Water Filtration via Solvent Vapor Treatment - Abd Halim, Nur Syakinah (Polymers (Basel), 2019)
Electrospun nanofiber membrane (NFM) has a high potential to be applied as a filter for produced water treatment due to its highly porous structure and great permeability. However, it faces fouling issues and has low mechanical properties, which reduces the performance and lifespan of the membrane. NFM has a low integrity and the fine mat easily detaches from the sheet. In this study, nylon 6,6 was selected as the polymer since it offers great hydrophilicity. In order to increase mechanical strength and separation performance of NFM, solvent vapor treatment was implemented where the vapor induces the fusion of fibers. The fabricated nylon 6,6 NFMs were treated with different exposure times of formic acid vapor. Results show that solvent vapor treatment helps to induce the fusion of overlapping fibers. The optimum exposure time for solvent vapor is 5 h to offer full retention of dispersed oil (100% of oil rejection), has 62% higher in tensile strength (1950 MPa) compared to untreated nylon 6,6 NFM (738 MPa), and has the final permeability closest to the untreated nylon 6,6 NFM (733 L/m(2).h.bar). It also took more time to get fouled (220 min) compared to untreated NFM (160 min).